Cytokinergic IgE Action in Mast Cell Activation - Bax, Heather J.; Keeble, Anthony H.; Gould, Hannah J. (Frontiers in Immunology, 2012)
Some ten years ago it emerged that at sufficiently high concentrations certain monoclonal mouse IgEs exert previously unsuspected effects on mast cells. Thus they can both promote survival and induce activation of mast cells without the requirement for antigens. This was a wake up call that appears to have been missed (or dismissed) by the majority of immunologists. The structural attributes responsible for the potency of the so-called “highly cytokinergic or HC IgEs” have not yet been determined, but the events that ensue when such IgEs bind to the high-affinity receptor, FcεRI, on mast cells have been thoroughly studied, and are strikingly similar to those engendered by antigens when they form cross-linked complexes with the receptors. We review the evidence for the cytokinergic activity of IgE, and the structural features and known properties of immunoglobulins, and of IgE in particular, most likely to be implicated in the phenomenon. We suggest that IgEs with cytokinergic activity may be generated by local germinal center reactions in the target organs of allergy. We consider also the important implications that the existence of cytokinergic IgE may have for a fuller understanding of adaptive immunity and of the action of IgE in asthma and other diseases.